NMDA receptor activation induces mitochondrial dysfunction, oxidative stress and apoptosis in cultured neonatal rat cardiomyocytes - Gao, X; Xu, X; Pang, J; C., Zhang; Ding, J. M; Peng, X; Liu, Y; Cao, Ji-Min (Physiological research, 2007)
Glutamate is a well-characterized excitatory neurotransmitter in the central nervous system (CNS). Recently, glutamate receptors (GluRs) were also found in peripheral tissues, including the heart. However, the function of GluRs in peripheral organs remains poorly understood. In the present study, we found that N-methyl-D-aspartate (NMDA) could increase intracellular calcium ([Ca2+]i) level in a dose-dependent manner in cultured neonatal rat cardiomyocytes. NMDA at 10-4 M increased the levels of reactive oxygen species (ROS), cytosolic cytochrome c (cyto c), and 17-kDa caspase-3, but depolarized mitochondrial membrane potential, leading to cardiomyocyte apoptosis. In addition, NMDA treatment induced an increase in bax mRNA but a decrease in bcl-2 mRNA expression in the cardiomyocytes. The above effects of NMDA were blocked by the NMDA receptor antagonist (+)-5-methyl-10,11-dihydro-5Hdibenzo[ a,d]cyclohepten-5,10-imine hydrogen maleate (MK-801), and by ROS scavengers glutathione (GSH) and N-acetylcystein (NAC). These results suggest that stimulation of NMDA receptor in the cardiomyocyte may lead to apoptosis via a Ca2+, ROS, and caspase-3 mediated pathway. These findings suggest that NMDA receptor may play an important role in myocardial pathogenesis.
Keywords: financování organizované; kaspasa 3; apoptóza; cytochromy c; techniky tkáňových kultur; oxidační stres; Myocytes, Cardiac; Apoptosis; Oxidative Stress; Mitochondrial Myopathies; vápník; Tissue Culture Techniques; Financing, Organized; mitochondriální myopatie; Cytochromes c; Receptors, N-Methyl-D-Aspartate; Calcium; receptory N-methyl-D-aspartátu; Caspase 3; kardiomyocyty